RESEARCH PUBLICATIONS IN LANGUAGE MAINTENANCE: AN OVERVIEW OF SCOPUS DATA IN 2009-2018 - Celya Intan Kharisma Putri (ETNOLINGUAL, 2020)
AbstractThis study used bibliometric analysis to investigate the study of language maintenance over a ten-year window to find out major publication trends in sociolinguistics and provide a systematic overview of the field in general. The report covers the number of published papers, numbers of citations, and the journal impact factor. In view of keywords, citation and reference data obtained from Scopus journal, this investigation performed three sorts of bibliometric evaluations to distinguish the prominent scientific papers, research institutions, authors, number of citations, geographic areas, and topic of research that have been exceptionally compelling in the field of sociolinguistics, especially about language maintenance over the last decade. Results show that the total 1399 publications related to language maintenance experienced a sharp increase in 2013 and 2015. Additionally, there was no significant relationship between the number of authors in a highly cited article and its number of citations. This paper will help researchers, students, and academicians who are interested in sociolinguistics filed. The findings offer information based on a bibliometric report about the present state of the literature and suggest a change in publication trends regarding the literature on the language maintenance and shift.Keywords: bibliometric analysis, language maintenance, sociolinguistics bibliometric, Scopus, SSCI. AbstrakPenelitian ini menggunakan analisis bibliometri untuk mengeksplorasi studi tentang pemeliharaan bahasa selama sepuluh tahun yang bertujuan untuk melihat tren publikasi utama dalam sosiolinguistik dan memberikan gambaran sistematis terkait bidang tersebut secara umum. Laporan data dalam artikel ini mencakup jumlah makalah yang diterbitkan, jumlah kutipan, dan faktor dampak jurnal. Berdasarkan kata kunci, sitasi dan data referensi yang diperoleh dari jurnal terindeks Scopus, penelitian ini memaparkan tiga macam evaluasi bibliometri untuk membedakan karya ilmiah terkemuka, lembaga penelitian, penulis, jumlah sitasi, wilayah geografis, dan topik penelitian yang menarik di bidang sosiolinguistik, terutama tentang pemeliharaan bahasa selama satu dekade terakhir. Hasil penelitian menunjukkan bahwa 1399 publikasi yang berkaitan dengan pemeliharaan bahasa mengalami peningkatan tajam pada tahun 2013 dan 2015. Selain itu, tidak ada hubungan yang signifikan antara jumlah penulis dalam artikel yang sangat banyak dikutip dan jumlah kutipannya. Artikel ini akan membantu peneliti, mahasiswa, dan akademisi yang berminat dalam bidang sosiolinguistik. Hasil penelitian memberikan informasi berdasarkan laporan bibliometri tentang keadaan literatur saat ini dan menunjukkan perubahan tren publikasi terkait literatur tentang pemeliharaan dan pergeseran bahasa.Kata kunci: analisis bibliometri, bibliometrik sosiolinguistik, pemeliharaan bahasa, Scopus, SSCI.